New Thinking, New Scholarship and New Research in Catholic Education Responses to the Work of Professor Gerald Grace - Whittle, Sean (Routledge Research in Education, 2021)
New Thinking, New Scholarship and New Research in Catholic Education gives a forum to many established and leading scholars to review and critically appraise the research contribution of Gerald Grace to Catholic education. The book demonstrates the way in which the field of Catholic Education Studies has developed under the influence of Grace, to become internationally recognised. This book demonstrates the ways in which Gerald Grace has shaped Catholic education since 1997. This begins with the primacy of empirical study and carefully conducted fieldwork when researching Catholic education. Many contributors focus on the way Grace champions the alignment between Catholic education and what we have come to know as the option for the poor. The collection also reflects Grace's intention to ensure the voices of women are properly represented in the field of Catholic education. The book is based on an inclusive and open principle that seeks to establish dialogue with educators of different faiths and different religious backgrounds, as well as secular and humanist critics. It will be of great interest to academics, scholars and students of religious education, the history of education and all those interested in the developing field of Catholic Education Studies.